2016
DOI: 10.1111/cei.12754
|View full text |Cite
|
Sign up to set email alerts
|

Serum properdin consumption as a biomarker of C5 convertase dysregulation in C3 glomerulopathy

Abstract: SummaryProperdin (P) stabilizes the alternative pathway (AP) convertases, being the only known positive regulator of the complement system. In addition, P is a pattern recognition molecule able to initiate directly the AP on non-self surfaces. Although P deficiencies have long been known to be associated with Neisseria infections and P is often found deposited at sites of AP activation and tissue injury, the potential role of P in the pathogenesis of complement dysregulation-associated disorders has not been s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 28 publications
0
29
0
Order By: Relevance
“…Ziegler et al . showed that higher levels of properdin were found in the urine of patients with renal disease vs healthy individuals, and Corvillo et al . proposed using serum properdin concentrations as a diagnostic marker for a subset of C3 glomerulopathy patients.…”
Section: Properdin Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Ziegler et al . showed that higher levels of properdin were found in the urine of patients with renal disease vs healthy individuals, and Corvillo et al . proposed using serum properdin concentrations as a diagnostic marker for a subset of C3 glomerulopathy patients.…”
Section: Properdin Sourcesmentioning
confidence: 99%
“…74 Mature neutrophils do not synthesize properdin but contain large stores of it in secondary granules, which are rapidly released upon stimulation with a variety of agonists, including C5a, fMLP, TNF-α, and IL-8. 75,76 A complete review of biological sources of properdin can be found in Cortes et al 71 Ziegler et al 78 showed that higher levels of properdin were found in the urine of patients with renal disease vs healthy individuals, and Corvillo et al 79 proposed using serum properdin concentrations as a diagnostic marker for a subset of C3 glomerulopathy patients. Studies are lacking, however, that shed light on the dynamics of properdin metabolism in the context of diseases that do not affect the kidney or that have excessive leukocyte activation or leukocyte dysfunction.…”
Section: Properdin Sourcesmentioning
confidence: 99%
“…FB levels may indeed be reduced in patients with C3NeF but this is not a constant finding. This issue has been debated in several works but there are heterogeneous results concerning FB levels in the published series [23][24][25]. During AP activation, in the absence of C3NeF, C3 and FB consumption are usually correlated; however, C3NeF breaks this correlation.…”
Section: Discussionmentioning
confidence: 99%
“…Serum C3 and C4 levels were measured by nephelometry (Siemens Healthcare, Erlangen, Germany). FB and P levels were measured using in-house ELISA assays, previously described by our group [23].…”
Section: Measurement Of the Levels Of Complement System Proteinsmentioning
confidence: 99%
“…The correlation between high terminal pathway activity and low serum levels of the positive AP regulator properdin observed in some C3G patients implies that the consumption of this factor in the circulation and its likely increased binding to the injured glomeruli may favor the formation of C5 convertases, thus contributing to higher C5 turnover in a subset of C3G patients, typically those with a C3GN pattern of diffuse, mostly mesangial deposits on electron microscopy [41]. Whereas the efficacy of anti-C5 therapy in other renal pathologies such as aHUS has been consistently higher, the poor outcomes in C3G may also reflect the recruitment of distinctly different pathological mechanisms in these renal disorders.…”
Section: C3 Glomerulopathy: Bridging the Gap Between Pathophysiolomentioning
confidence: 99%